Traditional and modern Japanese soy foods : manufacturing, nutrition and cuisine of a variety of soy foods for health and joy of taste - Ohyama, Takuji (Food Science and Technology, 2013)
In 2009, the average life span in Japan was 83 years old (women 86.08, men 79.29), which for women was the longest in the world. This may be partly due to the low fat Asian diet of rice, soybean products, fish and vegetables. Soybeans originated from East Asia, and Japanese people eat a variety of traditional foods made from soybeans, such as nimame (boiled soybean), irimame (baked soybean), tofu (soybean curd), abura-age (deep-fried soybean curd), shoyu (soy sauce), miso (fermented soybean paste), natto (soybeans fermented by bacteria), edamame (green vegetable soybean), and moyashi (soybean.